MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN KALIMAT SEDERHANA BAGI ANAK AUTIS MELALUI MEDIA FLIP CHART - Ricki Marta Putra (Universitas Negeri Padang, 2015)
ABSTRACT: The background of this research background by the apparent problems in the field, namely children Autism X class III in SLB sparkle Tarusan who have difficulty in reading comprehension simple sentence. This is evident from the beginning of the child's ability to undertake operations on a number of children have difficulty given problem. This study aims to improve the ability of autistic children to read a simple sentence comprehension through Flip Chart. Flip Chart is sheets of paper to resemble an album or calendar measuring 50 x 75 cm, or smaller size 21 x 28 cm, as Flipbook are arranged in the order that was tied at the top. The research methodology researchers use a single subject research design research using AB. That design study comparing the ability to understand the content of reading simple sentences in children with autism X between the baseline condition and the condition of intervention. The data analysis technique used is based on the observation data in the form of Visual Analysis of Graphs. he results of the study are analyzed include the number of observations in the baseline condition and meeting six times as much as eight times the intervention condition. The results of this study are shown in the analysis of data in the conditions and analysis of data between the conditions that indicate a change in the ability to read a simple sentence comprehension in children X towards a better. Analysis of data between the condition that the number of variables that change 1, change direction and effect positive trend (+), changes in the stability of the variable to variable, baseline conditions (A) 33%, 26%, 26%, 33%, 33%, 33% , conducted 6 (six) times pertmuan, intervention condition (B) 40%, 46%, 60%, 73%, 80%, 86%, 86%, 86%, made eight (8) meetings and the percentage of overlap 0%. From the results of the analysis of data obtained it can be concluded that the hypothesis (Ha) who submitted acceptable. That his sense that the media Flip chart can be used to improve the ability to read a simple sentence comprehension For Autistic child class III. Suggested for class teachers or subject teachers Indonesian to use Flip Chart for Autism in teaching children to read a simple sentence comprehension. Kata Kunci: Membaca Pemahamam, Autis, Media Flip Chart